Co-application of biochar and compost with decreased N fertilizer reduced annual ammonia emissions in wetland rice - Ferdous, J.; Mumu, N. J.; Hossain, M. B.; Hoque, M. A.; Zaman, M.; Müller, C.; Jahiruddin, M.; Bell, R. W.; Jahangir, M. M. R. (Frontiers in Sustainable Food Systems, 2023)
Ammonia (NH3) emission from rice fields is a dominant nitrogen (N) loss pathway causing negative impacts on farm profitability and the environment. Reducing N fertilizer application to compensate for N inputs in organic amendments was evaluated for effects on N loss via volatilization, rice yields and post-harvest soil properties in an annual irrigated rice (Boro) – pre-monsoon rice (Aus) – monsoon (Aman) rice sequence. That experiment was conducted using the integrated plant nutrition system (IPNS; nutrient contents in organic amendments were subtracted from the full recommended fertilizer dose i.e., RD of chemical fertilizers) where six treatments with four replications were applied in each season: (T1) no fertilizer (control), (T2) RD, (T3) poultry manure biochar (3 t ha−1; pyrolyzed at 450°C) + decreased dose of recommended fertilizer (DRD), (T4) rice husk ash (3 t ha−1) + DRD, (T5) compost (3 t ha−1) + DRD, and (T6) compost (1.5 t ha−1)+ biochar (1.5 t ha−1) + DRD. The N loss via volatilization varied twofold among seasons being 16% in irrigated rice and 29% in the pre-monsoon rice crop. In irrigated rice, T6 had significantly lower NH3 emissions than all other treatments, except the control while in pre-monsoon and monsoon seasons, T6 and T3 were alike. Pooling the three seasons together, biochar (T3) or biochar plus compost (T6) reduced NH3 loss via volatilization by 36-37% while compost alone (T5) reduced NH3 loss by 23% relative to RD. Biochar (T3) and biochar plus compost mixture (T6) reduced yield-scaled NH3 emissions by 40 and 47% relative to the RD of chemical fertilizer (T2). The organic amendments with IPNS reduced the quantity of N fertilizer application by 65, 7, 24, and 45% in T3, T4, T5, and T6 treatments, respectively, while rice yields and soil chemical properties in all seasons were similar to the RD. This study suggests that incorporation of biochar alone or co-applied with compost and decrease of N fertilizer on an IPNS basis in rice-based cropping systems can reduce N application rates and NH3 emissions without harming yield or soil quality.